Sobre la capacidad jurídica para reconocer hijos extramatrimoniales por los apoyos del padre o la madre en estado de coma, en el marco del Decreto Legislativo N° 1384 y la Convención sobre los Derechos de las Personas con Discapacidad - Príncipe Mena, Abner Hernán (2019)
Legislative Decree 1384 that recognizes and regulates the legal capacity of persons with disabilities on equal terms has marked a very important development of the regulatory framework of Family Law in our country, substantially strengthening it. Today, people in a coma through a judicially designated support can see their Human Rights optimized by exercising them by developing legal acts that until then were not allowed.